140k views
2 votes
1. Simplify this expression: 13+ (-12) - (-5) = ?

O A.-30
O B.6
O C.30
OD. -6

User Elvio
by
4.5k points

2 Answers

0 votes

Answer:

B)6

Explanation:

1) When solving an eqyation, always work from left to right

So

13-12=1

1-(-5)=6

*two negative signs like that make a positive*

Hope this helps!

User Vck
by
4.2k points
1 vote

Answer:

B.6

Explanation:

When we add and subtract, we do it from left to right

13+ (-12) - (-5)

13+-12

13-12 = 1

1 - -5

A negative negative is a positive

1 +5

6

User Ajay Pal Singh
by
4.3k points